The Role of Motor Activities in Acquiring Social Skills in Kindergarten Children From the Teachers' Perspective: An Analytical Study of Al-Intisar Kindergarten in Batin Al-Jabal (Al-Farooq Journal of Sciences, 2026)
This study sought to test and validate three main hypotheses derived from the following objectives: identifying and analyzing the impact of physical activities on the acquisition and development of communicative social skills, interactive social skills, and normative social skills (discipline-based skills) among children at Al-Intisar Kindergarten in Batin al-Jabal, from the perspective of female educators, The study employed a descriptive-analytical methodology, utilizing a questionnaire as the primary tool for data collection. The tool was applied to a research sample consisting of (25) educators at Al-Intisar Kindergarten, The findings validated the first hypothesis, confirming a statistically significant impact of physical activities on the acquisition and development of communicative social skills. Similarly, the second hypothesis was validated, showing a statistically significant impact on interactive social skills. However, the third hypothesis was refuted, indicating no statistically significant impact of physical activities on the development of normative social skills among the children from the educators' perspective, The study recommends developing physical activity programs in kindergartens and designing flexible, simplified games that enhance children's self-discipline and adherence to instructions. Furthermore, it emphasizes the necessity of cooperation between the family and the kindergarten to instill social skills, particularly normative ones, through role-modeling and practical application.
Keywords: Physical Activities, Social Skills, Kindergarten Child, Educators, Al-Intisar Kindergarten - Batin al-Jabal